2019
DOI: 10.1037/bul0000180
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the experimental evidence on the near- and far-transfer effects among children’s executive function skills.

Abstract: In the present meta-analysis we examined the near- and far-transfer effects of training components of children’s executive functions skills: working memory, inhibitory control, and cognitive flexibility. We found a significant near-transfer effect (g+ = 0.44, k = 43, p < .001) showing that the interventions in the primary studies were successful in training the targeted components. However, we found no convincing evidence of far-transfer (g+ = 0.11, k = 17, p = .11). That is, training a component did not have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
131
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(185 citation statements)
references
References 77 publications
15
131
3
2
Order By: Relevance
“…It has been proposed that early development may be the optimal time to intervene, before any negative effects fully embed (Heckman, 2006;Ramey & Ramey, 1998). A common approach to improving children's executive functions has been through cognitive training programs which directly target specific executive functions (Kassai, Futo, Demetrovics, & Takacs, 2019). Meta-analyses of studies with adults and older children indicate that training that targets working memory and inhibitory control can lead to improvements on trained constructs-so-called "near transfer"-but does not lead to improvements on untrained constructs, or "far transfer" (Kassai et al, 2019;Melby-Lerv ag & Hulme, 2013;Sala & Gobet, 2017;Schwaighofer, Fischer, & Buhner, 2015).…”
mentioning
confidence: 99%
“…It has been proposed that early development may be the optimal time to intervene, before any negative effects fully embed (Heckman, 2006;Ramey & Ramey, 1998). A common approach to improving children's executive functions has been through cognitive training programs which directly target specific executive functions (Kassai, Futo, Demetrovics, & Takacs, 2019). Meta-analyses of studies with adults and older children indicate that training that targets working memory and inhibitory control can lead to improvements on trained constructs-so-called "near transfer"-but does not lead to improvements on untrained constructs, or "far transfer" (Kassai et al, 2019;Melby-Lerv ag & Hulme, 2013;Sala & Gobet, 2017;Schwaighofer, Fischer, & Buhner, 2015).…”
mentioning
confidence: 99%
“…For instance, WM training does not enhance children's domain-general cognitive skills or academic achievement Melby-Lervåg et al, 2016;Sala & Gobet, 2020). The same applies to action and nonaction videogame training and brain training (Duyck & Op de Beeck, 2019;Kassai, Futo, Demetrovics, & Takacs, 2019;Libertus et al, 2017;Lintern & Boot, 2019;Sala, Tatlidil, & Gobet, 2018Simons et al, 2016).…”
Section: Beyond Meta-analytic Evidencementioning
confidence: 99%
“…Karbach and Verhaeghen examined the effects of process-based cognitive control training in older adults; their interventions resulted in promising transfer of the training effects, as significant medium to small-sized effects were observed in the performance of the trained task, neartransfer tasks, and far-transfer tasks [6]. However, studies have also shown that the transfer effect decreases with increasing distance between two tasks [24,[28][29][30][31]. Metaanalyses of transfer effects on cognitive control among children, young and older adults suggested a significant near-transfer effect and no convincing evidence of fartransfer [24,29,32].…”
Section: Behavioral Improvement and Transfer Effects Induced Bymentioning
confidence: 99%
“…However, studies have also shown that the transfer effect decreases with increasing distance between two tasks [24,[28][29][30][31]. Metaanalyses of transfer effects on cognitive control among children, young and older adults suggested a significant near-transfer effect and no convincing evidence of fartransfer [24,29,32]. The evidence from young adults indicates that working memory training did not elicit any improvements across all ranges of transfer [33], but produced short-term, specific training effects that do not generalize to measures of "real-world," such as intelligence, life ability, or academic performance [27,32].…”
Section: Behavioral Improvement and Transfer Effects Induced Bymentioning
confidence: 99%